2003
DOI: 10.1103/physrevlett.91.093602
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the Transfer of the Local Angular Momentum Density of a Multiringed Light Beam to an Optically Trapped Particle

Abstract: We observe the spinning and orbital motion of a microscopic particle trapped within a multiringed light beam that arises from the transfer of the spin and orbital components of the light's angular momentum. The two rotation rates are measured as a function of the distance between the particle and the axis of the trapping beam. The radial dependence of these observations is found to be in close agreement with the accepted theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
236
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 331 publications
(240 citation statements)
references
References 16 publications
3
236
1
Order By: Relevance
“…In particular, the orbital and spinning motions of probe particles in circularly-polarized vortex beams [15][16][17][18] originate exactly due to the force from the azimuthal component of p O and the torque from the longitudinal component of the spin density s. Furthermore, the quantum-mechanical resonant momentum transfer from light to a two-level atom is also determined by the canonical momentum density 37,38 . Finally, a remarkable recent experiment 36 , which realized quantum weak measurements of the local momentum of photons, also measured p O (ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the orbital and spinning motions of probe particles in circularly-polarized vortex beams [15][16][17][18] originate exactly due to the force from the azimuthal component of p O and the torque from the longitudinal component of the spin density s. Furthermore, the quantum-mechanical resonant momentum transfer from light to a two-level atom is also determined by the canonical momentum density 37,38 . Finally, a remarkable recent experiment 36 , which realized quantum weak measurements of the local momentum of photons, also measured p O (ref.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the spin s is proportional to the polarization helicity s and is also collinear with the wave vector. The optical momentum and spin densities can be measured experimentally by placing a small absorbing particle in the field and observing its linear and spinning motion [15][16][17][18][19] . Naturally, the radiation force and torque (with respect to the particle's centre) quantify the momentum and AM transfer to the particle and are proportional to the densities (2) in the plane wave (1): Fpp and Tps (refs 19-25), Fig.…”
mentioning
confidence: 99%
“…Recently, experimentalists [13,14] showed that the spin and orbital AM of a non-paraxial beam play distinct roles in the interaction with microscopic birefringent particles trapped off the beam axis in optical tweezers. It was observed [14] that the spin of light makes the particle rotate around its own axis and the orbital AM makes the particle rotate around the beam's axis.…”
Section: Introductionmentioning
confidence: 99%
“…This is accompanied by a steady improvement in particle manipulation techniques and theories [8][9][10][11][12][13][14], and by the use of spatially structured waves [15] with enhanced helicity [16] to increase the signal in circular dichroism [17,18] for enantiomeric discrimination [19][20][21]. In addition, recent studies [22] in fluorescence resonance energy transfer (FRET) [23,24], (see also [25,26]), show an electromagnetic force between excited molecules, different from the Van der Waals force when they are in their ground-state.…”
Section: Introductionmentioning
confidence: 99%